2015
DOI: 10.1111/1471-0528.13589
|View full text |Cite
|
Sign up to set email alerts
|

Continuation versus discontinuation of oxytocin infusion during the active phase of labour: a randomised controlled trial

Abstract: Objective To investigate whether discontinuation of oxytocin infusion increases the duration of the active phase of labour and reduces maternal and neonatal complications.Design Randomised controlled trial.Setting Department of Obstetrics and Gynaecology, Regional Hospital of Randers, Denmark.Population Women with singleton pregnancy in the vertex position undergoing labour induction or augmentation.Methods Two hundred women were randomised when cervical dilation was ≤4 cm to either continue or discontinue oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 26 publications
(61 reference statements)
3
31
2
1
Order By: Relevance
“…In contrary, study by Bor P et al 8 found the active phase of labour to be longer by 41 minutes in the discontinue group (Median 125 minutes) than in the continued group ( median 88 minutes), p value being 0.007 means significant difference.…”
mentioning
confidence: 75%
“…In contrary, study by Bor P et al 8 found the active phase of labour to be longer by 41 minutes in the discontinue group (Median 125 minutes) than in the continued group ( median 88 minutes), p value being 0.007 means significant difference.…”
mentioning
confidence: 75%
“…A previous meta-analysis of nine randomized controlled trials compared continuation and discontinuation of oxytocin after the active phase of labor and its effect on labor induction and labor augmentation [7][8][9][10][11][12][13][14][15]24]. In that meta-analysis, oxytocin discontinuation after the active phase of labor signi cantly lowered the cesarean delivery rate (9.3% vs 14.7%) and uterine tachysystole rate (6.2% vs 13.1%) compared with oxytocin continuation until delivery [24].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no consensus regarding the method of administration at the time of induction, it is common practice to adjust the dosage while observing uterine contractions to prevent adverse events. Recent reports have suggested that discontinuation of oxytocin infusion during the active phase of labor signi cantly lowered the risk of uterine tachysystole and cesarean delivery [7][8][9][10][11][12][13][14][15]. Uterine tachysystole is considered to affect fetuses with FGR more adversely than fetuses whose size is appropriate for gestational age (AGA).…”
Section: Introductionmentioning
confidence: 99%
“…37 Minimizing synthetic oxytocin use and considering decreasing or discontinuing use when active effective labor is established may help maximize oxytocin receptor availability such that women's uteri can respond to endogenous or exogenous postpartum oxytocin. [38][39][40] Strategies for prevention or quick repair of genital tract trauma should be a priority; 41 as it may be an overlooked driver of blood loss. 42 Finally, encouraging endogenous oxytocin release by assisting with early breastfeeding deserves further study.…”
Section: Discussionmentioning
confidence: 99%